KEDUDUKAN DAN FUNGSI INTERNAL AUDITOR PADA PT. EKASURYA MANDIRI BATAM - Bustanil Arif; Hendry Jaya (EQUILIBIRIA, 2014)
The Purposes of internal audit is to assist all members of management in carrying their duties effectively by providing objective data regarding the results of the analysis, assessment, recommendation and comments on the activities audited. To be able to work effectively with management, the internal auditor position greatly affects their success in performing the task. Internal audit should be placed such that it was possible to carry out those responsibilities properly and to ensure freedom in performing their duties.            Research by the author of the PT. Ekasurya Mandiri Batam in this thesis is to use descriptive qualitative method. This qualitative descriptive method is not based on a statistical calculation in the form of quantitative (amount) but in the form of a statement and a description of the subsequent analysis will be systematically compiled and then linked with the theories that have been there for the then newly drawn a conclusion.The results showed that the internal auditor position at PT. Ekasurya Mandiri Batam is independent and can achieve an objective examination. While the function of Internal Auditor at PT. Ekasurya Mandiri Batam can contribute to the achievement of good internal audit.